Chemical composition of essential oils of Achillea teretifolia Willd. and A. millefolium L. subsp. millefolium growing in Turkey - Kocak, Alpaslan; Bagci, Eyup; Bakoglu, Adil (Chemical Publishing Co., 2010)
The chemical composition of the essential oils of dried aerial parts of Achillea teretifolia and A. millefolium subsp. millefolium were analyzed by GC and GC-MS. Sixty seven and 57 components were identified representing 95.58 and 91.41% of the oils, respectively. 3-Cyclohexen-1-one (21.61%), linalool (14.32%), 1,8-cineole (12.71%), chrysanthenone (8.55%), trans-chrysanthenol (7.83%) and ?-cadinene (4.04%) were found to be the major components in A. teretifolia while ?-cadinene (19.03%), limonene oxide (10.13%), alloaromadendrene (6.37%), caryophyllene oxide (5.71%) and trans-caryophyllene (4.89%) were found as major constituents in A. millefolium subsp. millefolium.
Keywords: Achillea millefolium subsp. millefolium; Achillea teretifolia; Asteraceae; Essential oil composition; GC-MS